Kajian Teologis tentang Hikmat menurut Amsal 1: 7: Pedoman Etika bagi Pertumbuhan Iman Kristen - Sealtiel Daeli; Alfin Yunus Gulo; Malik Bambangan (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This article examines the concept of wisdom in Proverbs 1:7 as an ethical guideline for the growth of Christian faith. In the midst of modern challenges such as moral relativism, secularization, and the crisis of spiritual authority, a re-understanding of Biblical wisdom becomes a significant theological urgency. Through a hermeneutical-theological approach, this study integrates exegesis of the text of Proverbs 1:7 with contextual analysis and ethical reflection to show that the “fear of the LORD” is the epistemological and moral foundation of the believer's life. Wisdom, in the biblical sense, functions not only as a rational faculty, but also as a divine gift that shapes character, deepens relationship with God, and enables believers to live ethically in society. The results show that the growth of true Christian faith is reflected in an active spirituality and ethical actions that are rooted in a God-fearing relationship. Thus, Proverbs 1:7 is not only a theological basis, but also relevant as a practical principle in shaping an authentic and transformative Christian life in the contemporary era.